Comparative Study of the Physico- and Biochemical Properties of Two Types of Salted Japanese Apricot (Prunus mume) Pickles - Suwannachot, Jutalak; Ketnawa, Sunantha; Ogawa, Yukiharu (Frontiers in Sustainable Food Systems, 2021)
Two types of commercial salted Japanese apricot (ume) pickle products with different textures were studied and their physicochemical and biochemical properties compared. Considering the effects of fruit raw material ripeness and the pickle processing method, a pickled unripe-hard texture fruit (9% salinity) called “Karikari-ume” and a pickled ripe-soft texture ume fruit (10% salinity) called “Umeboshi” were used as sample materials. The results showed that the pH and moisture content of Karikari-ume (3.18% and 81.99%, respectively) was higher than that of umeboshi (2.84% and 74.08%, respectively). Meanwhile, the TSS and TA of citric acid and the TA of lactic acid value of the Karikari-ume (4.45%, 0.92%, and 1.30%, respectively) were lower than the Umeboshi (7.17%, 1.79%, and 2.52%, respectively). Karikari-ume also showed higher bioactive compounds and antioxidant activities assessed by DPPH•, ABTS•+, FRAP, and MIC assays (17.48–130.58 unit per gram of sample dry weight). These results suggested that the ripeness of the fruit material used in pickle processing could influence the physicochemical and biochemical properties of salted Japanese apricot pickles.